From Chalkboard Era to Digital Literacy Era: The Effect of Audio-Visual Tools on Modern Classroom at Islamic Secondary School Teachers in District Kot Addu - Muhammad Kashif Majeed; Tunku Badaraiah Binti Tunku Ahmad (Presscience, 2025)
The integration of audio-visual tools in modern classrooms has revolutionized traditional teaching methodologies, shifting from conventional chalkboard techniques to multimedia-based instruction. This study examines the impact of multimedia projectors on teaching effectiveness, student engagement, and learning outcomes compared to traditional methods. Utilizing a quantitative research design, data was collected from 500 secondary school teachers in District Kot Addu, South Pakistan, through a structured questionnaire. The analysis was conducted based on respondents' demographic characteristics to ensure a comprehensive evaluation. The findings reveal that multimedia projectors significantly enhance student engagement, comprehension, and retention of information. Teachers reported that the dynamic nature of audio-visual tools fosters an interactive learning environment, making complex concepts more accessible. However, the study also highlights challenges such as technical limitations, lack of training, and resistance to change, which hinder the seamless integration of these tools. Despite these obstacles, the research underscores the necessity of digital literacy in contemporary education, emphasizing the need for professional development programs to equip teachers with the necessary skills. Based on the findings, the study recommends targeted teacher training programs, improved access to multimedia resources, and strategic policy interventions to facilitate the adoption of technology in classrooms. By addressing these challenges, educational institutions can leverage audio-visual tools to create more engaging and effective learning experiences. This research contributes to the ongoing discourse on educational technology and provides insights for policymakers, educators, and institutions aiming to enhance teaching practices in the digital era.